STANDAR BAGI PENDIDIK DALAM STANDAR NASIONAL PENDIDIKAN INDONESIA - Helda Yanti; Syahrani (CV. ADIBA AISHA AMIRA (ADISAM PUBLISHER), 2025)
Education is the learning of knowledge, skills, and habits of a group of people that are passed down from one generation to the next through teaching, training, or research. Given the importance of education, especially one of the determinants of the final outcome of education is the performance of educators as the spearhead of the government dealing directly with students, it is very important to have standard educators